Long-Term Effects of Allogeneic Hematopoietic Stem Cell Transplantation on Systemic Inflammation in Sickle Cell Disease Patients - de Azevedo, Júlia Teixeira Cottas; Costa, Thalita Cristina de Mello; Lima, Keli Cristina; Maciel, Thiago Trovati; Palma, Patrícia Vianna Bonini; Darrigo-Júnior, Luiz Guilherme; Setanni Grecco, Carlos Eduardo; Stracieri, Ana Beatriz P. L.; Elias, Juliana Bernardes; Pieroni, Fabiano; Guerino-Cunha, Renato Luiz; Pinto, Ana Cristina Silva; et al. (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the only currently available curative treatment for sickle cell disease (SCD). However, the effects of HSCT on SCD pathophysiology are poorly elucidated. Here, we assessed red blood cell (RBC) adhesiveness, intensity of hemolysis, vascular tone markers and systemic inflammation, in SCD patients treated with allogeneic HSCT. Thirty-two SCD patients were evaluated before and on long-term follow-up after HSCT. Overall survival was 94% with no severe (grade III-IV) graft-vs-host disease and a 22% rejection rate (graft failure). Hematological parameters, reticulocyte counts, and levels of lactate dehydrogenase (LDH), endothelin-1 and VCAM-1 normalized in SCD patients post-HSCT. Expression of adhesion molecules on reticulocytes and RBC was lower in patients with sustained engraftment. Levels of IL-18, IL-15 and LDH were higher in patients that developed graft failure. Increased levels of plasma pro-inflammatory cytokines, mainly TNF-α, were found in SCD patients long-term after transplantation. SCD patients with sustained engraftment after HSCT showed decreased reticulocyte counts and adhesiveness, diminished hemolysis, and lower levels of vascular tonus markers. Nevertheless, systemic inflammation persists for at least five years after transplantation, indicating that HSCT does not equally affect all aspects of SCD pathophysiology.